Photon absorption and photocurrent in solar cells below semiconductor bandgap due to electron photoemission from plasmonic nanoantennas. (7th September 2012) - Novitsky, A.; Uskov, A. V.; Gritti, C.; Protsenko, I. E.; Kardynał, B. E.; Lavrinenko, A. V.
ABSTRACT We model the electron photoemission from metal nanoparticles into a semiconductor in a Schottky diode with a conductive oxide electrode hosting the nanoparticles. We show that plasmonic effects in the nanoparticles lead to a substantial enhancement in photoemission compared with devices with continuous metal films. Optimally designed metal nanoparticles can provide an effective mechanism for the photon absorption in the infrared range below the semiconductor bandgap, resulting in the generation of a photocurrent in addition to the photocurrent from band‐to‐band absorption in a semiconductor. Such structure can form the dais of the development of plasmonic photoemission enhanced solar cells. Copyright © 2012 John Wiley & Sons, Ltd.